2020
DOI: 10.1088/1755-1315/456/1/012038
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Staphylococcus aureus in wound infection on the skin surface

Abstract: Wound infection on the skin surface is colonized a wide variety of microorganisms. Microorganisms that cause inflammation of the skin surface is group of pyogenic bacteria. Staphylococcus aureus is one of the class of pyogenic bacteria that produce β-lactamase enzyme and eliminate the antibacterial activity, especially penicillin. The existence of this enzyme will destroy β-lactam ring, so that antibiotics become inactive. This study aimed to detect presence of Staphylococcus aureus on pus from wound infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…1 with S. aureus having the highest prevalence of 53% followed by S. epidermidis with 42% and S. pyogenes accounting for the least occurrence of 5%. This finding is cohesive with the observations from Almeida et al [14], Ekwati et al [15] and Baba et al [5] which confirm the prevalence of the same isolates in wounds of hospitalised patients. Ohabughiro et al [16] also reported the dominance of S. aureus and S. pyogenes in their study on orthopaedic wound infection in medical centres in South East Nigeria.…”
Section: Resultssupporting
confidence: 90%
“…1 with S. aureus having the highest prevalence of 53% followed by S. epidermidis with 42% and S. pyogenes accounting for the least occurrence of 5%. This finding is cohesive with the observations from Almeida et al [14], Ekwati et al [15] and Baba et al [5] which confirm the prevalence of the same isolates in wounds of hospitalised patients. Ohabughiro et al [16] also reported the dominance of S. aureus and S. pyogenes in their study on orthopaedic wound infection in medical centres in South East Nigeria.…”
Section: Resultssupporting
confidence: 90%
“…aureus. Moreover, Gram-negative bacteria such as Proteus sp., Aeromonas sp., and Escherichia sp. are also responsible for wound infections. , …”
Section: Resultsmentioning
confidence: 99%
“…are also responsible for wound infections. 51,52 The comparison of the antibacterial performance of the prepared biohybrid nanofibers based on myrrh@PVA/TG with some previously reported extract@nanofibers is summarized in Table 1. The antibacterial activity of myrrh@PVA/TG against Gram-negative bacteria was higher than that of the nanofibers in previous studies.…”
Section: In Vitro Antibacterial Assessment Of Electrospunmentioning
confidence: 99%
“…Propionibacterium grows well at pH 6.00-6.50 [48]. Staphylococcus aureus is a pyogenic bacteria [49]. S. aureus prefers a neutral pH environment for optimal growth and survival [50].…”
Section: Discussionmentioning
confidence: 99%